Sb2S3-based conversion-alloying dual mechanism anode for potassium-ion batteries - Shaokun Chong; Shuangyan Qiao; Xuedong Wei; Ting Li; Lingling Yuan; Shihong Dong; Wei Huang (iScience, 2021)
Summary: The large volume expansion and sluggish dynamic behavior are the key bottleneck to suppress the development of conversion-alloying dual mechanism anode for potassium-ion batteries (PIBs). Herein, Sb2S3 nanorods encapsulated by reduced graphene oxide and nitrogen-doped carbon (Sb2S3@rGO@NC) are constructed as anodes for PIBs. The synergistic effect of dual physical protection and robust C-Sb chemical bonding boosts superior electrochemical kinetics and great electrode stability. Thus, Sb2S3@rGO@NC exhibits a high initial charge capacity of 505.6 mAh·g−1 at 50 mA·g−1 and a great cycle stability with the lifetime over 200 cycles at 200 mA·g−1. Ex situ XRD, XPS, and TEM characterizations confirm that the electrode undergoes a multielectron transfer process (Sb2S3↔ Sb + K2S ↔ KSb + K3Sb), where K-ion insert into/extract from the material via dual mechanisms of conversion and alloying. This work sheds a light on the construction of high-performance anode materials and the understanding of K-ion storage mechanism.